GRAMMATICAL ERRORS IN UNDERGRADUATE STUDENTS’ RESEARCH PROPOSAL WRITING - Alberik Ryan Tendy Wijaya; Gracia Vica Ade Nugraheni; Barli Bram (Jurnal Bahasa Lingua Scientia, 2019)
The paper investigated common grammatical errors produced by Indonesian university students of English as a foreign language when writing their undergraduate research proposals. Accordingly, an urgent research question to resolve was what common grammatical errors are made by the seventh semester students of the English Language Education Study Program of Sanata Dharma University in writing Chapter One of their research proposals? To answer the research question, the researchers conducted a content analysis. The researchers analysed students’ research proposals, focusing on grammatical issues identified in the first chapter. Results showed that the errors were omission (content and grammatical morpheme), addition (double marking, regularization, and simple addition), misinformation (regularization errors, archi-forms, and alternating forms), misordering, parallelism and diction. The top three errors were successively omission (38.15 per cent), addition (21.97 per cent) and parallelism (18.5 per cent).